FRONTAL KNEE ANGLE DURING SINGLE LEG SQUAT AND VERTICAL DROP JUMP; A COMPARISON OF YOUTH ATHLETES WITH OR WITHOUT A HISTORY OF KNEE INJURY. Issue 7 (11th March 2014) - MacDonald, K; Whittaker, J; Baltich, J; Emery, CA
Abstract : Background: Knee joint injury has been associated with changes in hip and knee joint function and is a known risk factor for the development of post-traumatic osteoarthritis (PTOA). The Vertical Drop Jump (VDJ) and Single Leg Squat Test (SLS) have been used to examine lower extremity neuromuscular control. Objective: To determine if young adults with and without a 3–10 year history of knee joint injury differ in frontal knee angles or knee ankle ratio during VDJ and SLS. Design: Historical Cohort. Setting: Laboratory Setting. Participants: 25 individuals with history of intra-articular knee joint injury, sustained participating in sport 3–10 years previously, and 25 matched (age, sex, sport) uninjured controls (16 males;17–26 yrs: 34 females;14–26 yrs). Risk factor assessment: History or no history of intra-articular knee injury (clinical diagnosis resulting in time loss from sport). Main outcome measurements: Frontal knee angle (FKA) (degrees) and knee and ankle separation distances (KAR) were measured from an image representing the lowest moment of the SLS and VDJ extracted from video and measured using ImageJ (National Institute of Health, v.1.47) software. Test-retest reliability (sub-sample n=20) was examined (ICC) and descriptive statistics (means, 95%CI) used to compare study groups. Results: No differences in right to left FKA differential was found for the injured participants compared to matched controls during the SLS (ICC 0.97) [injured 5.78° (3.01, 8.54); uninjured 4.75° (1.85, 7.66) or VDJ (ICC 0.98) [injured 7.69° (2.58, 12.80); uninjured 9.64° (5.57, 13.70)]. Similarly, no between groups differences for KAR (ICC 0.99) were demonstrated [injured 1.00 (0.90, 1.09); uninjured 1.04 (0.97, 1.12)]. Conclusions: Individuals with a 3–10 year history of knee injury demonstrate similar FKA and KAR during the VDJ and SLS compared to healthy controls. These finding are encouraging as the functional joint changes associated with knee joint injury do not appear to be present in this timeframe post-injury.